POLA IMPLEMENTASI MODERASI BERAGAMA DALAM KONTEKS HETEROGENITAS AGAMA (ANALISIS DESA NAMO BINTANG DI KECAMATAN PANCUR BATU) - Pratama, Teguh Agum; Harahap, Nur Sapia (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
This article examines the pattern of religious moderation implementation in Namo Bintang Village, Pancur Batu District, North Sumatra, where the community life is marked by significant religious diversity. The urgency of this research lies in the need to understand how multicultural and multireligious societies can coexist peacefully amid differences in beliefs, an essential factor for social cohesion in Indonesia. Using a qualitative ethnographic approach, research data was collected through participatory observation, in-depth interviews, and documentation of social and religious activities within the community. The data analysis process utilized the Miles, Huberman, and Saldana model, including data reduction, presentation, and conclusion drawing or data verification, to ensure accuracy and validity. The research findings indicate that social life in Namo Bintang Village fosters religious harmony through various communal practices such as mutual cooperation (gotong royong), interfaith dialogue, and inclusive leadership by community leaders. These findings are discussed with reference to Judith Butler's Theory of Religious Performativity and Gordon Allport's Intergroup Contact Theory, revealing that religious moderation is not only reliant on formal policies but also shaped by the performance of social interactions and positive contact among diverse groups. In conclusion, the implementation of religious moderation in Namo Bintang Village shows that tolerance can be strengthened through constructive social contact and institutions that support inclusivity. As a recommendation, this model could be adapted to similar communities in Indonesia to reinforce social cohesion. It is also suggested that educational programs on tolerance and interfaith training be expanded as a foundation for sustainable religious moderation in diverse societies